2018
DOI: 10.3390/atmos9090340
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution, Bioaccessibility and Health Risks of Indoor/Outdoor Airborne Toxic Elements Collected from School Office Room

Abstract: 20 sets of indoor and outdoor size-segregated aerosol (SSA) samples (180 foils) were collected synchronously by using two 8 Stage Non-Viable Cascade Impactor from an office room in the central region of the megacity-Nanjing, China in winter and spring in 2016. The mass size distribution of SSAs was bimodal for outdoor SSAs and unimodal for indoor in both winter and spring. The crustal elements, such as K, Ca, Mg and Fe, were mainly distributed in the coarse fractions of SSAs while toxic elements such as As, Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Opposite to all the other elements, Sr showed an obvious increasing trend with the particle sizes and higher values were concentrated in the large particle sizes. Tang et al, (2018) studied the office indoor air in Nanjing and found that Sr was concentrated in the particles larger than 5.8μm. Tan et al, (2016) also found the mass concentration of Sr was enriched in the particles larger than 2.7μm in a high pollution episode during winter in Beijing.…”
Section: Segregated Particlesmentioning
confidence: 99%
“…Opposite to all the other elements, Sr showed an obvious increasing trend with the particle sizes and higher values were concentrated in the large particle sizes. Tang et al, (2018) studied the office indoor air in Nanjing and found that Sr was concentrated in the particles larger than 5.8μm. Tan et al, (2016) also found the mass concentration of Sr was enriched in the particles larger than 2.7μm in a high pollution episode during winter in Beijing.…”
Section: Segregated Particlesmentioning
confidence: 99%
“…The road tra c around a house is an important factor in uencing the heavy metal concentrations in indoor dust (Lin et al 2015). The burdens of Cd, Cu, Pb and Zn in areas with heavy tra c were reported signi cantly higher than those in other districts in Hong Kong, China (Tang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A database compiling indoor concentrations in office buildings was developed by including the results from 69 studies 19,21,25‐91 . Of these, 12 are reports from the French air quality monitoring network 55‐59,63‐67,70,71 .…”
Section: Methodsmentioning
confidence: 99%